EVALUASI PEMBELAJARAN SEJARAH PADA SMA NEGERI DI DKI JAKARTA - Umasih, Umasih (History Department, Semarang State University and Historian Society of Indonesia, 2012)
This article discusses the evaluation done by history teachers in high school in Jakarta, especially on the understanding of teachers about the evaluation of learning and the types and models of evaluation they perform. The instrument used to get the data s in the form of questionnaire given to 38 teachers from 152 people as the population using survey techniques. The results showed that most respondents (94.73%) understand the principles of competency-oriented evaluation. Evaluation after the implementation of KTSP (the curriculum at the level of education units) is different in quantity, form and manner about assessment. 23.69% of the respondents differ in quantity (frequency), the methods of evaluation and weighted score. Assessment given not only to answer the questions either multiple choice or essay, but students are also working on a quiz question, analyzing sources, practicing skills in developing mind mapping as well as a portfolio. While the types and models of assessment that are suitable for assessing history learning outcomes is the judgment that can measure cognitive and affective discourse up to the levels of analysis. Keywords: principles of evaluation, competence, and model evaluation Artikel ini membahas tentang evaluasi yang dilaksanakan guru-guru sejarah SMA NegeriÃ‚Â di DKI Jakarta, khususnya tentang pemahaman guru mengenai pelaksanaan evaluasi pembelajaran serta jenis dan model evaluasi apa yang dilaksanakannya. Instrumen yang digunakan untuk menjaring data berupa angket yang diberikan kepada 38 orang guru dari 152 orang sebagai populasi dengan menggunakan teknik survei. Hasil penelitian menunjukkan bahwa sebagian besar responden (94,73 %) memahami prinsip evaluasi yang berorientasi pada kompetensi. Pelaksanaan evaluasi sesudah pemberlakuan KTSP berbedaÃ‚Â dalam kuantitas, bentuk soal dan cara penilaian. 23,69 % responden menyatakan berbeda dalam kuantitas (frekuensi), cara penilaian dan bobot skornya. Penilaian yang diberikan bukan hanya menjawab soal-soal baik pilihan ganda maupun essay, tetapi siswa juga mengerjakan soal kuis, menganalisis sumber, keterampilan dalam menyusun mind mapping (peta pikiran) serta menyusun portofolio. Sedangkan jenis dan model penilaian yang cocok untuk menilai hasil pembelajaran sejarah adalah penilaian yang dapatÃ‚Â mengukur ranah kognitif dan afektif hingga tingkatan analisis. Kata kunci : prinsip evaluasi, kompetensi, jenis dan model evaluasi Ã‚Â